Agricultures familiales et pouvoirs publics au Brésil : les étapes d’une reconnaissance - Claire Cerdan (Bulletin de l’Association de Géographes Français)
In this paper, we analyze the institutional and organizational factors which have influenced the development of policies and mobilizations around family farmers in Brazil. We identify the main steps and the different instances involved in the recognition and promotion of family farmers. We then focus on programs and policies which consider the integration of family farmers into the national and international markets. Finally, we relate limitations and hesitations in the ways to think public actions modalities; it is an invitation to rethink the models of agricultural development.